Cocaine Use and Inflammation Is Associated with Diet Quality in People Living with HIV (PLWH) from the MASH Cohort. (29th May 2020) - Martinez, Sabrina Sales; Hernandez, Jacqueline; Martin, Haley; Tamargo, Javier; Teeman, Colby; Johnson, Angelique; Huang, Yongjun; Campa, Adriana; Baum, Marianna
Abstract: Objectives: Cocaine use is one of the most widely used illicit drugs in Miami, FL and especially among PLWH. Cocaine use is associated with greater systemic inflammation and poor dietary intake. Lifestyle factors such as diet may influence inflammation and further exacerbate the effects of substance use and HIV infection on systemic inflammation. This study examined the relationships of cocaine use, inflammation and diet quality in PLWH from the Miami Adult Studies on HIV (MASH) cohort. Methods: After obtaining informed consent, data on demographics, socioeconomic status, substance use and parameters of HIV disease progression (CD4 cell count and HIV viral load) were collected from 50 participants enrolled in the MASH cohort in Miami, FL. A total of 4 to 5 24-hour recalls were collected for each participant. Diet quality was assessed using the USDA Healthy Eating Index (HEI)-2015. Interleukin 6 (IL-6) was measured using the Quantikine ELISA kit (R&D Systems, Minneapolis, MN). Statistical analyses used descriptive statistics, Spearman's correlations, Mann-Whitney U and logistic regression. Results: The participants' mean age was 55 ± 6.81, 58% were male, and 68% were African Americans. Overall the diet quality was low with a total median HEI-2015 score of 44.5 (IQR = 38.8–53.8), lower than the general US population score of 59 ( P  < 0.001) and it was not significantly correlated with IL-6 scores (r = −0.212, P  = 139). Cocaine users had significantly lower total median HEI scores [41 (IQR = 35–48) vs.45 (IQR = 41–57.50), P  = 0.048] than cocaine non-users. Component HEI scores of whole fruit (r = −0.280, P  = 0.049) and saturated fat (r = −0.341, P  = 0.015) were correlated with IL-6. Moreover, lower saturated fat intake reduced odds of having IL-6 above the median (OR = 0.710, 95% CI: 0.544–0.928, P  = 0.012), after controlling for age, sex, income, education, and cocaine use. Conclusions: Diet quality was low for all the participants and significantly lower for those who used cocaine compared to non-users. Higher inflammation was associated with lower fruit and higher saturated fat intakes. Larger studies are needed to elucidate these relationships in order to develop appropriate interventions for PLWH. These results highlight the need for nutritional counseling for PLWH, especially if the condition is associated with cocaine use. Funding Sources: NIDA and NIMHD.